Strategi Pengelolaan Risiko Dalam Mengatasi Keterlambatan Pemahaman Peserta Didik di Lembaga Pendidikan di SD Juara Bandung - Triana, Risa; Wahyu Hidayat (Education Management: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to identify the factors influencing students’ comprehension delays and the learning strategies implemented to address them. A qualitative research method was used, collecting data through interviews, observations, and documentation. Findings indicate two main factors affecting comprehension delays: limited knowledge and student behavior. Implemented strategies include regular study programs, Tilawah Tahfidz Qur’an (TiTiQ), Camp Training at Darul Qur’an, Adab Class, Seven Habits (7 Habits), Core Values, and extracurricular activities. These strategies are expected to reduce comprehension delays and enhance students’ cognitive, character, and spiritual development.